2015
DOI: 10.14687/ijhs.v12i2.3300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of instruction based on realistic mathematics education on mathematics achievement: A meta-analysis study<p>Gerçekçi matematik eğitimi destekli öğretimin matematik başarısına etkisi: Bir meta-analiz çalışması

Abstract: The purpose of this research is to determine the overall effect of instruction based on realistic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…In this regard, it can be stated that the RME-based teaching has a positive effect on the mathematical achievement of students. This finding is in agreement with the findings of Kaplan et al (2015)…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this regard, it can be stated that the RME-based teaching has a positive effect on the mathematical achievement of students. This finding is in agreement with the findings of Kaplan et al (2015)…”
Section: Discussionsupporting
confidence: 94%
“…Meta-analysis allows a coherent process of gathering and interpreting the results of individual studies conducted independently from each other (Cohen, Manion, & Morrison, 2007). When the literature is examined, it can be seen that a study by Kaplan, Duran, Doruk, and Öztürk (2015) brings…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the analysis of the effect of RME on the variables with which it was studied, it was concluded that RME was effective in almost all of the studies. Studies supporting this result obtained from the research are available in the literature (Çelik 2013;Doğan ve Kurt, 2019;Kaplan et. al, 2015;Tabak, 2019, Özdemir, 2020, Tamur, Juandi and Adem 2020Turgut, 2021).…”
Section: Results Discussion and Implicationssupporting
confidence: 66%
“…This situation has created the idea that awareness of RME will increase in mathematics education research. It is possible to find some review studies that articles and postgraduate studies conducted on the field of RME approach were analyzed apart from the studies on RME applications (Doğan and Kurt, 2019;Kaplan, Duran, Doruk and Öztürk, 2015;Özdemir, 2020;Tabak, 2019;Turgut, 2021). This study which more studies have been analyzed deeply compared to the literature will contribute to the literature in terms of uncovering the overall tendency and the inadequacies in the field of RME In this study, it was aimed to analyze the articles and the thesis deeply published between 2010 and 2021 in the field of Realistic Mathematics Education (RME) according to the specified criteria.…”
Section: Introductionmentioning
confidence: 99%